Complex variation in habitat selection strategies among individuals driven by extrinsic factors - Raynor, E. J.; Beyer, H. L.; Briggs, John M.; Joern, Anthony (My University, 2017)
Understanding behavioral strategies employed by animals to maximize fitness in the face of environmental heterogeneity, variability, and uncertainty is a central aim of animal ecology. Flexibility in behavior may be key to how animals respond to climate and environmental change. Using a mechanistic modeling framework for simultaneously quantifying the effects of habitat preference and intrinsic movement on space use at the landscape scale, we investigate how movement and habitat selection vary among individuals and years in response to forage quality-quantity tradeoffs, environmental conditions, and variable annual climate. We evaluated the association of dynamic, biotic forage resources and static, abiotic landscape features with large grazer movement decisions in an experimental landscape, where forage resources vary in response to prescribed burning, grazing by a native herbivore, the plains bison (Bison bison bison), and a continental climate. Our goal was to determine how biotic and abiotic factors mediate bison movement decisions in a nutritionally heterogeneous grassland. We integrated spatially explicit relocations of GPS-collared bison and extensive vegetation surveys to relate movement paths to grassland attributes over a time period spanning a regionwide drought and average weather conditions. Movement decisions were affected by foliar crude content and low stature forage biomass across years with substantial interannual variation in the magnitude of selection for forage quality and quantity. These differences were associated with interannual differences in climate and growing conditions from the previous year. Our results provide experimental evidence for understanding how the forage quality-quantity tradeoff and fine-scale topography drives fine-scale movement decisions under varying environmental conditions.
Citation: Raynor, E. J., Beyer, H. L., Briggs, J. M., & Joern, A. (2017). Complex variation in habitat selection strategies among individuals driven by extrinsic factors. Ecology and Evolution, 7(6), 1802-1822. doi:10.1002/ece3.2764
Keywords: Bison Bison; Climatic Variability; Forage Maturation Hypothesis; Forage; Quality-Quantity Tradeoffs; Konza Prairie